2019
DOI: 10.1111/jomf.12573
|View full text |Cite
|
Sign up to set email alerts
|

Informal Networks of Low‐Income Mothers: Support, Burden, and Change

Abstract: Objective The authors examined the support and burden of low‐income, urban mothers' informal networks. Background Living or growing up in poverty strongly predicts barriers and instability across several life domains for mothers and their children. Informal networks can play a critical role in promoting maternal and child well‐being particularly in the midst of poverty. Understanding informal support and the reciprocal burden it may create is especially relevant for low‐income families living with a reduced pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Of course, financial support is not always available or evenly distributed within families, and other family members may constitute a source of burden rather than benefit (AUTHORS, under review). Likewise, support may come at a cost, such that the obligations of reciprocity can become a strain in themselves (see Radey & McWey, 2019). However, for present purposes, we are interested in first establishing if families can be a potential source of identity-based support in times of financial adversity.…”
Section: A Social Identity Approach To Financial Resiliencementioning
confidence: 99%
“…Of course, financial support is not always available or evenly distributed within families, and other family members may constitute a source of burden rather than benefit (AUTHORS, under review). Likewise, support may come at a cost, such that the obligations of reciprocity can become a strain in themselves (see Radey & McWey, 2019). However, for present purposes, we are interested in first establishing if families can be a potential source of identity-based support in times of financial adversity.…”
Section: A Social Identity Approach To Financial Resiliencementioning
confidence: 99%
“…In line with the COR theory, single mothers' poor mental health seems to result mainly from the losses of material and social resources, but these adverse effects of resource loss, or the threat of resource loss, may be balanced by received or expected resource gains (Hobfoll, 2001). Accordingly, support from relatives and other social networks is one of the key coping strategies for single mothers (Radey & McWey, 2019;Taylor & Conger, 2017).…”
Section: The Conservation Of Resources (Cor) Theorymentioning
confidence: 87%
“…Most scholars attribute the mental health disadvantage of single mothers to the chronic economic strains many of them are exposed to, as well as social stressors associated with single-parenting responsibilities (Dziak et al, 2010). Among single mothers, mobilizing support within networks of family members and relatives is one of their key coping strategies (Radey & McWey, 2019;Taylor & Conger, 2017). Grandparents are often the most important source of this support, and there is evidence that grandparents provide more support to their adult children who are single parents than to their partnered children (Cooney, 2020;Dunifon et al, 2018), and that adult children also receive more help from their own parents when going through separation (Min et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To test the longitudinal influence of maternal safety nets on child behavior problems, we created a variable based on Radey and McWey's (2019) latent class analysis using the WCF to distinguish among mothers without support or manageable obligations, those with manageable obligations only, those with support only, and those with support and manageable obligations. As hypothesized from Taylor and Conger's (2017) extended family stress model, the parallel process latent growth curve model indicated that mothers with healthy safety nets had children with fewer behavior problems.…”
Section: Discussionmentioning
confidence: 99%
“…For support, mothers indicated whether they had “no one,” “some,” or “enough” support in each area. For obligations, mothers indicated whether they had “no one,” “too many,” “only a few,” or “as many as you can handle.” Following Radey and McWey (2019), we dichotomized support (enough/some vs. none) and obligations (as many as you can handle/only a few [i.e., manageable] vs. too many/no one) to distinguish between mothers who had at least some support in each area and a manageable level of obligation in each area. From these dichotomies, we created a four‐level variable of total net for this study: (0) no support or manageable obligations, (1) manageable obligations only, (2) support only, and (3) support and manageable obligations.…”
Section: Methodsmentioning
confidence: 99%